Ketidakpastian geopolitik global dan implikasinya terhadap ketahanan ekonomi indonesia - Fitriana, Nuzul (Maliki Interdisciplinary Journal, 2026)
Current global geopolitical dynamics are marked by uncertainty stemming from the Russia-Ukraine conflict, tensions in the Middle East, and strategic rivalry between the United States and China. These conditions have systemic implications for the global economy, including Indonesia, through surging commodity prices, disruptions in global supply chains (Global Value Chains), inflation, and financial market instability. This article aims to analyze the implications of this uncertainty for national economic resilience and Indonesia’s geostrategic role in addressing it. The study is conducted through the Wawasan Nusantara perspective, which views Indonesia’s geographical position as both a strategic asset and a vulnerability to the spillover effects of regional and global conflicts. The findings indicate that Indonesia addresses these challenges through a geostrategy manifested in National Resilience, through a strategy of free and active diplomacy, strengthening regional cooperation via ASEAN, as well as digital economic transformation and self-reliance in the food and energy sectors. In conclusion, strengthening economic resilience is a concrete step toward national resilience in safeguarding sovereignty and the welfare of the people amid dynamic international turmoil.